Evaluación de la transferencia tecnológica del proyecto "Servicios de conservación forestal” en 3 comunidades de la cuenca del río Itaya, distrito de Belén, región Loreto. 2020 - Terrones Gomez, Danny (2022)
The theme was "Evaluation of the technology transfer of the "Forest Conservation Services" project in 3 communities of the Itaya river basin, Belén district, Loreto region." 2020. The project in question began in 2018, so it turned out to do the evaluation to verify if there was progress or setbacks in it. The type of research was descriptive, cross-sectional. Simple probabilistic sampling was used randomly, where the sample of 45 beneficiaries (15 per community) was selected. The results obtained from the survey ballots were interpreted through descriptive statistics. As results were obtained; They have little knowledge of the concept of agroforestry system; They consider that group techniques such as technical talks were the ones with the highest participation (100%) due to the short time allocated (1 day from 3 to 5 hours), greater training time and less attendance. After the training, the application of the contents is little (57.77%) and putting into practice what has been learned is little (66.67%). Regarding the level of adoption of transferable practices, they only adopted nursery management (77.78%) and application of planting densities (88.89%); many practices are accepted but not adopted. Consequently, a low adoption level of project practices (88.88) is considered, considering that the practices taught are subsequently applied (80%) and partially (71.11%). They do not apply the same due to ignorance of the technique (22.22%) and lack of resources (48.88%). It is concluded that the transfer for the adoption of the proposed technology is not the most optimal, due to the results observed.